Wild genius - domestic fool? Spatial learning abilities of wild and domestic guinea pigs - Lewejohann, Lars (BioMed Central, 2010)
BACKGROUND: Domestic animals and their wild relatives differ in a wide variety of aspects. The process of domestication of the domestic guinea pig (Cavia aperea f. porcellus), starting at least 4500 years ago, led to changes in the anatomy, physiology, and behaviour compared with their wild relative, the wild cavy, Cavia aperea. Although domestic guinea pigs are widely used as a laboratory animal, learning and memory capabilities are often disregarded as being very scarce. Even less is known about learning and memory of wild cavies. In this regard, one striking domestic trait is a reduction in relative brain size, which in the domesticated form of the guinea pig amounts to 13%. However, the common belief, that such a reduction of brain size in the course of domestication of different species is accomplished by less learning capabilities is not at all very well established in the literature. Indeed, domestic animals might also even outperform their wild conspecifics taking advantage of their adaptation to a man-made environment. In our study we compared the spatial learning abilities of wild and domestic guinea pigs. We expected that the two forms are different regarding their learning performance possibly related to the process of domestication. Therefore wild cavies as well as domestic guinea pigs of both sexes, aged 35 to 45 days, were tested in the Morris water maze to investigate their ability of spatial learning. RESULTS: Both, wild cavies and domestic guinea pigs were able to learn the task, proving the water maze to be a suitable test also for wild cavies. Regarding the speed of learning, male as well as female domestic guinea pigs outperformed their wild conspecifics significantly. Interestingly, only domestic guinea pigs showed a significant spatial association of the platform position, while other effective search strategies were used by wild cavies. CONCLUSION: The results demonstrate that domestic guinea pigs do not at all perform worse than their wild relatives in tests of spatial learning abilities. Yet, the contrary seems to be true. Hence, artificial selection and breeding did not lead to a cognitive decline but rather to an adaptation to man-made environment that allows solving the task more efficiently.